SOME APPLICATIONS OF CAUCHY’S MEAN VALUE THEOREM - Lozada-Cruz, German [UNESP] (SCIK Publishing, 2020)
In this note we prove some applications of Cauchy’s mean value theorem.
Keywords: bounded linear operator; Cauchy’s mean value theorem; Wachnicki’s theorem